Miłość Boga w nauczaniu Jana Pawła II - Kunka, Sławomir (Verbum Vitae, 2013)
To talk about God’s love is to talk about God Himself, because “God is love” (1 John 4:8). God’s love for men is, in the teaching of John Paul II, the foundation of the papal proclamation. Its source is the inner love of the Holy Trinity. The present article discusses the statement of St. John, who says that “God is love” (1 John 4:8). This statement speaks of the essence of God in the aspect of Trinity’s inmost being and in terms of the economy of salvation. The article also takes up the issue of love of the Father and of the Son, and the question of the Holy Spirit as the Love of the Father and the Son. The Third Person of God, coming from the Father and the Son, is the Breath of Their mutual Love.